Development of High Dose Oseltamivir Phosphate Dry Powder for Inhalation Therapy in Viral Pneumonia - Shahir Aziz; Regina Scherlieβ; Hartwig Steckel (MDPI AG, 2020)
Oseltamivir phosphate (OP) is an antiviral drug available only as oral therapy for the treatment of influenza and as a potential treatment option when in combination with other medication in the fight against the corona virus disease (COVID-19) pneumonia. In this study, OP was formulated as a dry powder for inhalation, which allows drug targeting to the site of action and potentially reduces the dose, aiming a more efficient therapy. Binary formulations were based on micronized excipient particles acting like diluents, which were blended with the drug OP. Different excipient types, excipient ratios, and excipient size distributions were prepared and examined. To investigate the feasibility of delivering high doses of OP in a single dose, 1:1, 1:3, and 3:1 drug/diluent blending ratios have been prepared. Subsequently, the aerosolization performance was evaluated for all prepared formulations by cascade impaction using a novel medium-resistance capsule-based inhaler (UNI-Haler). Formulations with micronized trehalose showed relatively excellent aerosolization performance with highest fine-particle doses in comparison to examined lactose, mannitol, and glucose under similar conditions. Focusing on the trehalose-based dry-powder inhalers' (DPIs) formulations, a physicochemical characterization of extra micronized grade trehalose in relation to the achieved performance in dispersing OP was performed. Additionally, an early indication of inhaled OP safety on lung cells was noted by the viability MTT assay utilizing Calu-3 cells.